How to Expedite Rehabilitation Without Jeopardizing Litigation - Glass, Jesse T. (1986)
Where litigation and rehabilitation become enmeshed, doctors may have to face problems both complex and stressful. When disabling injuries occur, law and medicine must work together in the best interests of the client/patient. This paper offers specific advice to doctors who are called upon to give evidence concerning the state of health or prognosis of patients involved in litigation arising from disabling injury.